(untitled) (Heritage, 2024)
Internet-mediated online communication, particularly with regard to a product, brand, or organization, is known as electronic word-of-mouth (eWOM). Analyzing this open exchange of opinions and information about a company or product among consumers can be extremely useful for businesses. Opinion mining, (sentiment analysis), is a popular subdomain in Natural language processing (NLP) which allows for transforming qualitative data into quantitative information. The sentiment analysis of eWOM has greatly improved with the advancement of artificial intelligence (AI). Nowadays, computer algorithms can automatically classify the sentiment polarity of digital communication after extracting plain text. Artificial intelligence (AI) has the potential to fundamentally alter how companies assess and use consumer feedback to improve their products and services. In this paper, the authors, by analysing the attitudes of 450 respondents, tried to bring this current topic closer to experts in the field of digital marketing, in order to point out to them all the benefits that the sentiment analysis of consumers with the help of artificial intelligence algorithms can provide. The aim of this study is to indicate that if marketing experts use sentiment analysis supported by artificial intelligence (AI), they will be able to gain deeper insights on their customers and adjust their business strategies accordingly.